Assessment of 11 Exploited Fish and Invertebrate Populations in the Japan Sea Using the CMSY and BSM Methods - Zhang, Shanshan; Wang, Yibang; Wang, Yuanchao; Liang, Cui; Xian, Weiwei (Frontiers in Marine Science, 2020)
The catch-maximum sustainable yield (CMSY) method and a closely related Bayesian state-space Schaefer surplus production model (BSM) were combined with published catch data and catch per unit effort (CPUE) time series or spawning stock biomass (SSB) data to evaluate fisheries reference points for exploited resources of the Japan Sea. Eleven fish and invertebrate stocks were assessed; outcomes obtained through this analysis were the carrying capacity, biomass trajectory, maximum sustainable yield, and related parameters of each stock. Results showed that the stock of Arctoscopus japonicus was slightly overfished; the stocks of Cleisthenes pinetorum, Hippoglossoides dubius, Paralichthys olivaceus, and Chionoecetes opilio were overfished; and the stocks of Eopsetta grigorjewi, Pagrus major, Gadus chalcogrammus, and Glossanodon semifasciatus were grossly overfished; Pseudopleuronectes herzensteini was proved to be severely depleted; only Pandalus eous was in good condition. These results are consistent with the few previous studies on the status of fish species around the Japan Sea, where overfishing is becoming increasingly apparent. These assessments provide a basis for guiding the use, management, and rebuilding of fishery resources in the Japan Sea.